Islam, Budaya, dan Komunikasi Publik: Sinergi Pemimpin Aceh dalam Meningkatkan Partisipasi Masyarakat di Era Digital - Hariadi, Joko; Sazali, Hasan; Amelia, Nur (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
Aceh as a province rich in its Islamic heritage and local culture, is faced with a major challenge in enhancing civic participation through the utilisation of digital technology. This research aims to identify the important role of Acehnese leaders in utilising digital media to strengthen Islamic values and local culture, as well as increase community engagement in the development process. The method used is a qualitative approach through a literature review that focuses on analysing various relevant sources, such as scientific journals, books, and reports related to public communication in Aceh. The results show that Acehnese leaders have successfully utilised social media and other digital platforms to spread religious and cultural messages in line with Islamic teachings, which in turn encourages community participation in various social and political activities. However, challenges remain related to the digital divide and uneven understanding among the public. The findings emphasise the importance of Aceh's leaders in bridging this gap with a more inclusive approach.